A LITERRATURE REVIEW : VARIASI UBI JALAR SEBAGAI ALTERNATIF PANGAN DARURAT - Amirullah, M Fadil; Afifah, Diana Nur; Noer, Etika Ratna (Journal of Nutrition College, 2024)
ABSTRACTBackground: Emergency food is a practical and highly nutritious alternative intake. Meanwhile, the nutritional content of emergency food must be 2,100 kcal daily. Limited food supplies due to disasters also result in malnutrition for disaster victims. Some nutritional problems that arise during disasters include malnutrition at vulnerable ages and decreased nutritional status in community groups. Based on this, practical, nutritious food that can be consumed directly is needed. One of the local food ingredients that can be used to make emergency food is sweet potatoes. Objective: This research aims to determine variations of sweet potato as an alternative ingredient in making emergency food. Results: The development of emergency food based on local food can be an effort to overcome the problem of lack of food availability. One food ingredient that can be used as emergency food is sweet potatoes. Sweet potatoes contain minerals and vitamins such as potassium, phosphorus, vitamin C, vitamin K, and Vitamin B, and fiber. Several processed products developed using purple sweet potato as emergency food include biscuits, food bars, noodle snack bars, and jalangkote. Conclusion: The benefits of sweet potatoes as emergency food can be used as alternative food, based on processed products developed using sweet potatoes as emergency food. This study also emphasizes sweet potatoes as a nutritious and practical food source for disaster victims at a relatively low price and easy to obtain. Keywords: emergency food; sweet potato; local food  ABSTRAKLatar belakang: Pangan darurat merupakan alternatif asupan yang praktis dan bernutrisi tinggi. Adapun, kandungan nutrisi dalam pengan darurat adalah harus memenuhi sebesar 2.100 kkal per hari. Keterbatasan bahan pangan karena bencana berakibat pula pada kekurangan gizi korban bencana. Beberapa masalah gizi yang muncul ketika bencana diantaranya adalah kurang gizi pada usia rentan hingga menurunnya status gizi pada kelompok masyarakat. Berdasarkan hal tersebut maka diperlukan pangan yang praktis dan bergizi serta bisa langsung dikonsumsi. salah satu bahan pangan lokal yang dapat digunakan sebagai pembuatan pangan darurat adalah ubi jalar.Tujuan: Penelitian ini bertujuan untuk variasi ubi jalar sebagai alternatif bahan dalam pembuatan pangan darurat. Hasil: Pengembangan pangan darurat berbahan dasar pangan lokal mampu menjadi upaya dalam mengatasi masalah kurangnya ketersediaan makanan. Salah satu bahan makanan yang dapat dijadikan sebagai pangan darurat adalah ubi jalar. Ubi jalar tersebut mengandung mineral dan vitamin seperti kalium, fosfor, vitamin C, vitamin K dan Vitamin B serta terdapat pula kandungan serat. Beberapa produk olahan yang telah dikembangan menggunakan bahan ubi jalar ungu sebagai pangan darurat diantaranya adalah biskuit, food bar, snack bar, mie . Simpulan: Manfaat ubi jalar seebagai pangan darurat bisa dijadikan sebagai pangan alternatif hal ini didasari dengan adanya olahan produkyang telah di kembangkan menggunakan ubi jalar sebagai pangan darurat. Kajian ini juga meenenkankan ubi jalar sebagai sumber pangan bergizi dan praktis bagi para korban bencana dengan harga relatif murah dan gampang di dapatkan.Kata Kunci : pangan darurat; ubi jalar; pangan lokal